HAJI DAN KEGAIRAHAN EKONOMI:: Menguak Makna Ibadah Haji Bagi Pedagang Muslim di Yogyakarta - M. Sulthoni; Muhlisin; Muthoíin (JURNAL PENELITIAN, 2012)
Haj is an exclusive and unique worship. It is exclusive because not all Muslims do not have to that. This ritual is only done by those who have the physical ability, psychological, and financial requirements to run it. Hajj ritual is unique because it often goes beyond the normative boundaries. The phenomenon of pilgrimage draper in Beringharjo market that is the subject of this study clearly demonstrate this. The traders set aside a portion of the liver berrela trading profits earned every day, collecting little by little in a long time, and after a relatively large collected was not used to expand the business as usual by merchants, but "spent" to perform Hajj. This study found the base rationalization traders in the market Beringharjo which can be traced from three aspects, namely the meaning of the Hajj, the use of pilgrims symbols, and the use of these symbols in their trading activities. First, the meaning of Hajj has at least four different meanings, namely: (a) normative meaning; (b) the pilgrimage is a guarantee for answered prayer; (c) the Hajj is a symbol of high social and cultural status; (d) the symbol of Hajj is a trust assurance to buyers. Second, the creation of the symbolic aspects of the pilgrims in Beringharjo market traders motivated by three things, namely cultural, social, and economic background. Third, widening, shifting and expanding the meaning of Hajj which is influenced by religious backgrounds, worldviews as Javanese, and its position as a trader.